Urgensi Pemahaman Bahasa Arab dalam Mempelajari Agama Islam di Indonesia - Agustini Agustini (UIN Sunan Kalijaga Yogyakarta, 2021)
Arabic is a foreign language in Indonesia, most of those who study Arabic in Indonesia are predominantly Muslim. Arabic is one of the languages of communication and also the language of religion. Some people in Indonesia study Arabic only as a science of language while Arabic is associated with the language of religion because the population in Indonesia is predominantly Muslim, therefore most Muslims in Indonesia learn Arabic to make it easier to understand the contents of the holy book Al-Qur'an 'an and to explore the religious side. The type of research used is descriptive qualitative which will clearly narrate the data obtained in the field. This study aims to determine the importance of understanding the Arabic language for Muslim communities in Indonesia. Learning Arabic requires carefulness and seriousness since the tools of knowledge acquired in Arabic will not be easily understood in a short learning time. The holy book of Islam is the Koran written in Arabic. Therefore, one who wants to understand Islam well is highly recommended to study Arabic seriously as the most impossible thing he can do. That is because by learning Arabic, he will be able to understand every meaning of Islamic teachings contained in the holy book Al-Qur'an which has been written in Arabic. Al-Qur'an and hadith are the main sources of implementing Islamic teachings, Thus, if a Muslim understands Arabic well enough then understanding both Qur'an and hadith will definitely be easier and can also prevent him from misunderstanding or misinterpreting the content. Therefore, in Islamic Education, Arabic language education is very important to be taught. Arabic is not only the language of Muslims but the language that Allah has chosen as the language of the Qur'an. The urgency of learning Arabic is very important in Islamic education in order to be able to understand the teachings contained in Islamic education.